Review of Gioula Koutsopanagou, The British Press and the Greek Crisis, 1943–1949: Orchestrating the Cold-War "Consensus" in Britain - Hassiotis, Loukianos (Historein, 2025)
Review of Gioula Koutsopanagou, The British Press and the Greek Crisis, 1943–1949: Orchestrating the Cold-War “Consensus” in Britain. London: Palgrave Macmillan, 2020. 375 pp.